Effect of soil tillage on diversity and abundance of macrofungi associated with chestnut tree in the northeast of Portugal - Baptista, P. (2005)
European chestnut trees (Castanea sativa Mill.) have a great economic interest for wood and fruit production in the northeast of Portugal. In order to maintain the soil free of weeds, farmers traditionally practice several superficial tillages along the year. Phytosanitary problems mainly related with increasing Phytophtora cinnamomi contamination of soils are progressively changing these practices. In this context, the present work intends to evaluate the effect of two different soil management (tillage vs. non-tillage) of chestnut orchards on the macrofungi diversity and abundance. During Autumn-Winter 2003, two neighbors C. sativa orchards were selected, one tilled and one non-tilled. In each orchard, five plots of 100 m² were delimited and weekly all mushrooms, mycorrhizal and non-mycorrhizal, were harvested. The collected sporocarps were identified and quantified in order to evaluate the biodiversity and abundance of species. In this study, 50 macrofungi species belonging to 20 genera were identified. In tilled orchard 17 species from 12 genera were harvested, mainly from the genera Russula, Macrolepiota, Laccaria, and Inocybe. Non-tilled orchard showed higher number of species (47) and genera (17), belonging the greater number of species observed to the genera Russula, Inocybe, Cortinarius, Tricholoma, and Laccaria. These results suggest that soil tillage practices decreased significantly the total number of species and the number of mycorrhizal and non-mycorrhizal mushrooms in chestnut orchards.